Research on a Marine Animal Behavior Recording Tag System Based on Combined Positioning and Recovery - Chuan Tian; Shiyao Shen; Zejin Sun; Dazhen Xu; Peng Luo; Yuanjie Song; Zhentong Wang; Chen Wang; Shengzong Zhang; Chong Shen (Journal of Marine Science and Engineering)
The ocean represents the cradle of life on Earth, making it essential to comprehend the complex interactions between marine animal behaviors and the physical microstructure of their environments in order to study their behavioral ecology. Due to the vastness of the ocean, traditional observational techniques are constrained by distance, which poses significant challenges for conducting extended and continuous research on marine animal behavior and ecology. To overcome these challenges, this paper introduces a behavior recording tag system incorporating temperature, pressure, and miniature inertial measurement unit (MIMU) sensors as data collection modules. These sensors are integrated with a main control module and a data storage module to gather and archive behavioral and environmental information. A combined positioning recovery method is proposed, developed, and validated to address the issue of retrieving the tag system post data collection. The behavior recording tag system’s performance was assessed through laboratory and pool tests. The findings show that the accuracy of temperature sensor is about 0.01 °C, the accuracy of pressure sensor is approximately 0.5% of full scale, the continuous data collection duration can extend to 3 days, and the recovery window time after surfacing exceeds 7 days, underscoring its viability as a marine animal behavior recorder.